Chemical composition and in vitro antiplasmodial activity of the total alkaloids of the bulbs of two amaryllidaceae species from Northern Peru - Soto-Vásquez M.R. (2021)
We thank the Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica (FONDECYT) del Consejo Nacional de Ciencia Tecnología e Innovación Tecnologica (CONCYTEC-Perú) Grants Nº 110 -2018 - FONDECYT, for financial support to this study. The authors thank the Programa Iberoamericano de Ciencia y Tecnología para el Desarrollo (CYTED) for providing the framework.